Peran Pos Bantuan Hukum (POSBAKUM) dalam Penanganan Perkara Perceraian bagi Masyarakat Tidak Mampu di Peradilan Agama - Faizah, Kuni; Widiyanto, Hari; M. Mustahal (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Legal Aid Post (Posbakum) is a legal aid institution funded by the state through religious courts. This institution aims to provide free legal aid for people who cannot afford to get justice. This study uses a descriptive analysis method to examine the role, challenges, and effectiveness of Posbakum in handling divorce cases. Posbakum at the Purworejo Religious Court has a strategic role in helping the community, especially the less fortunate, to access justice in divorce cases. Posbakum services include free legal consultations, document assistance, and legal information. However, several challenges such as lack of public awareness, limited understanding, and ineffective coordination with related parties still need to be overcome. Research shows that the main causes of divorce in Purworejo are prolonged conflict, financial (economic) problems, and domestic violence. In order to improve the effectiveness of Posbakum in handling divorce cases, the existing challenges must be overcome immediately. Although Posbakum has a very strategic role, efforts still need to be made to improve its performance in helping the community, especially in matters of divorce